2000
DOI: 10.1038/sj.onc.1203332
|View full text |Cite
|
Sign up to set email alerts
|

Glutamic acid mutagenesis of retinoblastoma protein phosphorylation sites has diverse effects on function

Abstract: The retinoblastoma tumor suppressor gene (Rb) has many functions within the cell including regulation of transcription, dierentiation, apoptosis, and the cell cycle. Regulation of these functions is mediated by phosphorylation at as many as 16 cyclin-dependent kinase (CDK) phosphorylation sites in vivo. The contribution of these sites to the regulation of the various Rb functions is not well understood. To characterize the eect of phosphorylation at these sites, we systematically mutagenized the serines or thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…By contrast, sham-transduced KRC cells were either refractory to TGF-β1 (KRC1017) or were growth stimulated (KRC1022-4) (Supplemental Figure 4B). Moreover, we found that transfection with a construct encoding RB in which all potential phosphorylated sites were mutated to glutamate (25) did not restore TGF-β1-mediated growth inhibition ( Figure 2F). Thus, functional RB is necessary for the cytostatic functions of TGF-β1 in KRC cells, consistent with previous findings in fibroblasts (26).…”
Section: Resultsmentioning
confidence: 93%
“…By contrast, sham-transduced KRC cells were either refractory to TGF-β1 (KRC1017) or were growth stimulated (KRC1022-4) (Supplemental Figure 4B). Moreover, we found that transfection with a construct encoding RB in which all potential phosphorylated sites were mutated to glutamate (25) did not restore TGF-β1-mediated growth inhibition ( Figure 2F). Thus, functional RB is necessary for the cytostatic functions of TGF-β1 in KRC cells, consistent with previous findings in fibroblasts (26).…”
Section: Resultsmentioning
confidence: 93%
“…67 Nevertheless, cumulative effects of different phosphorylations of pRb, including other phosphorylations specifically ascribed to CDK4 such as Ser780, appear to be required to abolish E2F-binding and cell cycle inhibition. 55,65,68 By contrast, inhibition of pRb binding to LXCXE-containing proteins depends on phosphorylations of Thr821 and/or Thr826, while phosphorylation of Ser807 and/or Ser811 is required to abolish pRb binding to, and inhibition of, the nuclear tyrosine kinase c-Abl. 10 Beside their overlapping effects on E2F-binding and cell cycle progression associated with phosphorylation of pRb at Ser780 and Ser795 and possibly other sites, cyclin D1 might thus differ from cyclin D3 by its higher capacity to modulate other pRb functions via Ser807/811 phosphorylations.…”
Section: Discussionmentioning
confidence: 99%
“…[71][72][73][74] In a background of six other phospho-mimetic mutations, the glutamic acid mutation of Ser807/811 suffices to completely prevent the differentiationpromoting function of pRb in Saos-2 cells. 68 An intriguing possibility thus remains that the more restricted pRb-kinase activity of cyclin D3 could preserve some differentiation-related functions of pRb, and thus support specialized cell cycles involved in the proliferation of cells undergoing or maintaining differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study utilizing glutamic acid mutagenesis of the Rb protein employed phosphorylation site mutants that contained different combinations of between 1-12 altered sites. 24 However, this study measured the role of phosphorylation sites in the processes inhibit JNK/SAPK. In fact, JNK/SAPK exhibits kinase activity toward T821 of Rb in the presence of full-length Rb, 43 suggesting that while Rb inhibits JNK/SAPK pro-apoptotic activity, JNK/ SAPK, in turn, promotes the anti-apoptotic activity of Rb by the phosphorylation of T821.…”
Section: Discussionmentioning
confidence: 99%
“…22 Mutagenesis of Rb has been utilized to study the function of specific phosphorylation sites of Rb, 23,24 which has led to the identification of roles for certain sites in specific processes. 25,26 These studies highlight the complexity of Rb regulation by phosphorylation, showing that specific Rb phosphorylation sites (or groups of sites) are responsible for the regulation of the diverse functions of Rb.…”
Section: Introductionmentioning
confidence: 99%